2005
DOI: 10.1093/bja/aei232
|View full text |Cite
|
Sign up to set email alerts
|

Influence of changing work patterns on training in anaesthesia: an analysis of activity in a UK teaching hospital from 1996 to 2004 † †This article is accompanied by the Editorial.

Abstract: The reduction in total operating theatre cases for our trainees was evident across the epochs analysed, case numbers fell after introduction of the New Deal as well as more recently following the WTD, particularly for SHOs who are now doing a larger proportion of their work at night. SHOs and SpRs are doing more obstetric cases than in previous times but these are regional and not general anaesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 1 publication
3
33
3
Order By: Relevance
“…Overall, however, there has been a 27% reduction in their median number of theatre sessions (Table 1). This is similar to the 21% and 18% caseload reductions reported by two previous regional studies [12,13]. The issue for debate is whether or not the needs of senior trainees should be regarded as different from those of junior trainees and that in fact, they need more independent practice than supervised practice.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall, however, there has been a 27% reduction in their median number of theatre sessions (Table 1). This is similar to the 21% and 18% caseload reductions reported by two previous regional studies [12,13]. The issue for debate is whether or not the needs of senior trainees should be regarded as different from those of junior trainees and that in fact, they need more independent practice than supervised practice.…”
Section: Discussionsupporting
confidence: 84%
“…Although much of the evidence in anaesthesia supports the notion that clinical caseload has declined since the introduction of the Directive [12][13][14], Al-Rawi and Spargo have reported no reduction in caseload or proportion of supervision in their department since the Directive's implementation [15].…”
Section: This Article Is Accompanied By An Editorial See P 937 Of Tmentioning
confidence: 99%
“…Training is one thing, performance another. Concerns have been raised over a perceived increase in airway complications in UK anaesthetic practice, particularly in obstetric anaesthesia [9,14,22,23]. In the latest CEMACH report, anaesthesia-related deaths increased, and all were associated with general anaesthesia [14].…”
Section: The Problemmentioning
confidence: 99%
“…11 Search of the references of these studies identified another 14 citations. With further analysis, articles were selected wherein interventions relevant to one or more of the three themes were studied, resulting in a final selection of 56 citations Twenty-one studies analyzed transitions in, during, and after residency education; 19 studies addressed the educational effects of duty hour limits, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and 16 articles presented research on use of the competencies in teaching and assessing anesthesiology residents. [19][20][21][22][23][24][25][26][27][52][53][54][55][56][57][58] For the theme ''duty hours and the acquisition of competence'', the only articles included were those that assessed the effect of duty hour limits on measures of physician competence and those that studied changes in patient care experience in anesthesiology that could be attributed to the reduction in resident hours.…”
Section: Methodsmentioning
confidence: 99%
“…46,47 In one study, reduced opportunities for training with faculty and reduced perceived competence were found, 34 and no change was shown in four studies. [48][49][50][51] There is a considerable lack of high-quality studies that focus on the effect of duty hour limits on the competence of anesthesiologists after completion of training. In studies on the effect of the limits on surgical training, the hours in operative and perioperative training totalled only slightly more than 5,000 hours or somewhat more than one-fourth of the 19,200 hours in five years of surgical training with an 80-hour work week.…”
Section: Duty Hour Limits and The Acquisition Of Competencementioning
confidence: 99%